PERLINDUNGAN HUKUM TERHADAP PERUSAHAAN TRANSPORTASI ONLINE DALAM TINDAK PIDANA PENIPUAN ORDER FIKTIF - Arif Hidayat Giawa; Batara Andri Futra Situmorang; Willy Tanjaya (jurnal.unprimdn.ac.id, 2019)
Online-based transportation was created with the aim of making it easier for someone who wants to travel easily to order, be efficient and effective. In carrying out its activities there are problems that harm the online transportation companies, namely fictitious orders. Fictitious orders are classified as fraudulent acts. Online transportation companies have the right to obtain legal protection. The form of legal protection that must be given to online transportation companies is: compensation, termination of employment and punishment. This study uses legal normative juridical research. The results of this study indicate that those who bear the loss of the company are those who have committed fictitious order fraud, namely the online driver. So that in this case the company can sue the driver regarding the fictitious order.